‘One-Day-Wide’ Canada: History, Geography, and Aerial Views at Trans Canada Air Lines, 1945-1955 - Stein, Blair (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2018)
This article shows how Trans Canada Air Lines (now Air Canada) navigated celebrating Canada’s geography while eliminating it using modern communications technologies in its midcentury public-facing material. TCA worked explicitly with modern and high-modern discourse of “space” and “time,” manipulating the historical and geographic imaginary to position itself as a natural part of the Canadian envirotechnical landscape. In so doing, TCA also self-fashioned as the gatekeeper of geographic experiences in the form of aerial views. By embracing a new technological system—aviation—and a new type of environment—the geographic imaginary—this article pushes the boundaries of envirotech and argues that the Canadian tendency towards both geographic and technological nationalism is, at its center, an envirotechnical relationship.